Moonlighting Behavior: Theory and Evidence - Karen Smith Conway; Jean Kimmel (W.E. Upjohn Institute for Employment Research, 1992)
Two labor supply issues that have received substantial attention are the responsiveness of labor supply to wage changes and the imposition of labor supply constraints. Adjusting hours worked on a second job may be the practical and perhaps only available response to either event yet, most labor supply studies only examine behavior on the primary job. Examining the motives for moonlighting provides evidence on both the wage-responsiveness of labor supply in general and the existence and consequences of labor supply constraints. If, for instance, workers moonlight only when constrained on their primary jobs, then moonlighting itself implies that labor supply constraints exist and so supports the previous literature that incorporates these constraints (e.g. Hamm 1982, 1986). Regardless of the motive for moonlighting, allowing for potential labor supply adjustments on more than one job may very will alter the much-accepted conclusion regarding the inelasticity f male labor supply (for surveys, see Killingsworth 1983 or Pencavel 1986). By ignoring moonlighting behavior, researchers may be eliminating the most significant avenue for short term labor supply adjustments. Our research substantially improves the manner in which moonlighting is examined, and in so doing sheds new light on male labor supply elasticities. Specifically, we devise a theoretical model that permits different reasons for moonlighting and considers moonlighting in tandem with labor supply behavior on the primary job. Estimating both primary and secondary job hours equations using panel data from the SIPP (Survey of Income and Program Participation ) for prime-aged men, we find evidence that the decision to moonlight is quite responsive to wage changes (on both jobs) and arises from at least two distinct motives. Furthermore, properly modeling primary job hours constraints and differences in moonlighting motives reveals that the desired labor supply of prime-aged males is much more wage-elastic than typically assumed. Why do some people choose to moonlight? The predominant view is that it results from a constraint on hours worked on the primary job (Shishko and Rostker (1976), O'Connell (1979) and Krishnan (1990)). Due to workweek restrictions, economic conditions or other institutional factors, the worker is unable to work (or earn) as much as he or she desires on the primary job (PJ), and may thus consider taking a second job. The decision to moonlight hinges on a comparison between the reservation wage and the wage earned on a second job (SJ). The reservation wage and, there fore, the decision to moonlight will depend in part on the number of hours worked on the primary job. A major shortcoming of the aforementioned studies is the inclusion of (exogenous) primary job hours in moonlighting equations estimated for all workers (even non-moonlighters), many of whom may be unconstrained on their primary jobs. Indeed, estimating hours worked on the PJ as a choice variable is the purpose of a great many labor supply studies. To treat is as fixed and exogenous for all workers in inconsistent with basic economic theory and will likely lead to biased parameter estimates. Our econometric model corrects this misspecification and predicts which workers are constrained on their primary jobs. Another explanation for moonlighting behavior is that labor supplied to different jobs may not be perfect substitutes or, put differently, the age paid and utility lost form the foregone leisure may not completely reflect the benefits and costs to working. For example, working on the primary job may provide the worker with the credentials to take on a higher paying second job, such as a university professor who engages in consulting. Or, working on the second job may provide some pleasure (or less displeasure) but pay less than the primary job, such as a musician who has a "regular" job by day and performs at night. In either example, the costs and benefits of both jobs are more complex than the monetary wages paid and the forgone value of leisure. When faced with such nonpecuniary benefits and costs, optimizing behavior may lead a worker to take two jobs. Whereas Shishko and Rostker (1976) and others acknowledge that such a motive may exist, only Lilja (1991) explores it theoretically and empirically. Using Finnish data, the author finds evidence that this second motive better explains male moonlighting behavior that the first, more popular view. We build on Lilja's work by constructing a more consistent theoretical model and by explicitly modeling the behavior on the first job. Our research examines moonlighting behavior recognizing that workers may moonlight because of constraints on their primary jobs or because the two jobs are heterogeneous. We make no a priori assumptions regarding the existence of PJ constraints. We choose the SIPP data for our empirical analysis because it has detailed information on the second job that is superior to that available in other surveys (namely the panel Study of Income Dynamics, National Longitudinal Survey, and Current Population Survey), and it has a short (four month) survey period that permits us to better observe worker movements into and out of jobs. Cross-sectional data likely understate the true degree of moonlighting. In sum, our results help answer the questions of who moonlights and why, as well as provide new evidence of the wage-responsiveness of labor supply on both jobs and the prevalence of labor supply constraints.
Keywords: J0; J2; 330; moonlighting; second; jobs; labor; Conway; Kimmel